Trained Immunity for Personalized Cancer Immunotherapy: Current Knowledge and Future Opportunities - Lérias, Joana R.; de Sousa, Eric; Paraschoudi, Georgia; Martins, João; Condeço, Carolina; Figueiredo, Nuno; Carvalho, Carlos; Dodoo, Ernest; Maia, Andreia; Castillo-Martin, Mireia; Beltrán, Antonio; Ligeiro, Dário; et al. (Frontiers in Microbiology, 2020)
Memory formation, guided by microbial ligands, has been reported for innate immune cells. . Epigenetic imprinting plays an important role herein, involving histone modification after pathogen-/danger-associated molecular patterns (PAMPs/DAMPs) recognition by pattern recognition receptors (PPRs). Such ‘trained immunity’ affects not only the nominal target pathogen, yet also non-related targets that may be encountered later in life. The concept of trained innate immunity warrants further exploration in cancer and how these insights can be implemented in immunotherapeutic approaches. In this review, we discuss our current understanding of innate immune memory and we reference new findings in this field, highlighting the observations of trained immunity in monocytic and natural killer cells. We also provide a brief overview of trained immunity in non-immune cells, such as stromal cells and fibroblasts. Finally, we present possible strategies based on trained innate immunity that may help to devise host-directed immunotherapies focusing on cancer, with possible extension to infectious diseases.